Economic Evaluation of Vertical Photovoltaic System on High-rise Building in Malaysia - Ghazali, A.; Salleh, E.; Lim, C. H.; Sopian, K.; Mat, S. (Journal of Advanced Research in Business and Management Studies, 2020)
In order to provide sufficient information to the designer, investor and the end user regarding the implementation of the photovoltaic system on building façade, forecasting energy generation and cost involved is required. Using System Advisor Model developed by National Renewable Energy Laboratory. This paper focuses on the financial evaluation of vertical photovoltaic façade system on a high-rise building in Malaysia based on 5 possible design scenarios using amorphous silicon heterojunction module with a nominal efficiency of 15.6%. Based on the financial analysis the payback period for the vertical photovoltaic system in Malaysia is about 12 years while the horizontal system is 6 years. On a monthly average, PV system on vertical façade able to save about MYR 33,000 to 68,000 each month compared to PV on roof installation is about MYR 21,000 each month. This shows that photovoltaic on vertical façade of a high-rise building can potentially be implemented in Malaysia climate condition and with carefully design approach, its can open a new demographic in Malaysian built environment and Renewable Energy industries.